Happiness from What We Have and What We Experience: Attribute Non-alignability Increases Anticipated Satisfaction from Experiential Purchases - Kim, Minhee; Ahn, Hee-Kyung (ASIA MARKETING JOURNAL, 2020)
This research examines how processing type and alignability moderate the effect of product type on satisfaction (i.e., happiness). It is well known that there are two types of processing―deliberative and intuitive processing. Based on the previous literature that the intuitive processing is compatible with experiential purchases and the deliberative processing is fit with material purchase, the current research demonstrates that processing type moderates the effect of product type on happiness. Moreover, we hypothesize that alignability moderates the effect of product type on anticipated satisfaction. As expected, participants in the intuitive processing condition reported greater happiness from their experiential purchases than material purchases. However, in the deliberative processing condition, there was no significant difference between happiness levels from material and experiential purchases. Furthermore, when the attributes of choice options were presented in a non-alignable manner, participants reported greater anticipated satisfaction from experiential purchases than from material purchases. However, this difference disappeared when attributes were presented in an alignable manner. Finally, we propose ‘choice process’ satisfaction as a potential mediator of the moderating effect of processing type on the relationship between product type and (anticipated) satisfaction.